PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA TENAGA KERJA PROYEK PEMBANGUNAN GEDUNG MTsN II BOJONEGORO - Ayu Kurnia Ratna Sari (Litbang Pemas - Universitas Islam Lamongan, 2017)
The purpose of the study were 1) to describe motivation ,and work environment on performance of building construction project personnel MTsN II Bojonegoro., 2) to determine and analyze the simultaneous effect of simultaneous motivation and working environment significantly against performance of building construction project personnel MTsN II Bojonegoro , 3) to determine and analyze the partial effect motivation and working environment significantly to the performance of building construction project personnel MTsN II Bojonegoro, 4) to determine and analyze between , motivation, and working environment has dominant influence towards performance of building construction project personnel MTsN II Bojonegoro.This research was conducted with a population of as many as 27 respondents. Data were collected using a questionnaire in the form of a statement list. Data analysis technique used is the multiple linear regression analysis using SPSS 17.0. Based on the results obtained regression analysis test F value of 11.128 with a signification level of 0.000, which means that simultaneous motivate and work environment has a significant influence on the performance of.The value of building construction project personnel MTsN II Bojonegoro coefficient of determinant of = 0.481 means that 48.1% of medical personnel’s performance can be explained by the motivation and the environment and the rest 51.9% influence by other variables beyond the motivation and work environment.t value variable motivation () of 3.239 with a significance level of 0.003. t value variable environment () amounted to 2.516 with significance level of 0.003